1996
DOI: 10.1001/archinte.1996.00440140123012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hormone Replacement Therapy on Lipoprotein(a) and Lipid Levels in Postmenopausal Women

Abstract: High concentrations of lipoprotein(a) [Lp(a)], an independent risk factor for atherosclerosis, cannot be managed by the usual lipid-lowering agents. It has been suggested that Lp(a) levels are related to female sex hormones. Estrogen replacement therapy makes the lipid profiles favorable for delaying atherosclerosis in postmenopausal women. The effects of the combination therapy of estrogen and progesterone on lipids are controversial. This study was designed to evaluate the effect of female sex hormones on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…SG and raloxifene both produced a marked reduction in serum triglyceride concentrations. Since the administration of estrogen to postmenopausal women increased triglyceride levels [26] and changes in triglyceride levels were negatively associated with changes in estradiol levels in premenopausal women [27], it follows that changes in triglyceride concentrations in our study must be related with changes in body weight. A trend to a progressive increase in body weight during menopausal transition is closely associated with an increase in total cholesterol and LDL cholesterol levels, and no change in HDL cholesterol levels [27].…”
Section: Discussionmentioning
confidence: 95%
“…SG and raloxifene both produced a marked reduction in serum triglyceride concentrations. Since the administration of estrogen to postmenopausal women increased triglyceride levels [26] and changes in triglyceride levels were negatively associated with changes in estradiol levels in premenopausal women [27], it follows that changes in triglyceride concentrations in our study must be related with changes in body weight. A trend to a progressive increase in body weight during menopausal transition is closely associated with an increase in total cholesterol and LDL cholesterol levels, and no change in HDL cholesterol levels [27].…”
Section: Discussionmentioning
confidence: 95%
“…Equilin, also known as 7-dehydroestrone, is a natural estrogenic steroid synthesized in pregnant mares and used together with estrone and equilenin for hormone replacement therapy in postmenopausal woman to reduce coronary artery disease. Equilin modifies lipid profiles in patients and obtains neuroprotective and antioxidant activity ( 52 54 ). Here we found that equilin markedly suppresses the growth of UBE3D-deleted xenografts in mice as a 3βHSD1 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…et Haines et al, 1996;Kim et al, 1996;Hänggi Blood samples for measurement of serum Lp(a), oestradiol and et Espeland et al, 1998;Spencer et al, 1999).…”
Section: The Administration Of Oral Oestrogens In Postmenopausalmentioning
confidence: 99%